The rights and freedoms gradient of health: evidence from a cross-national study - Bezo, Brent; Maggi, Stefania; Roberts, William L. (Frontiers in Psychology, 2012)
This study examined the combined influences of national levels of socioeconomic status, social capital, and rights and freedoms on population level physical and mental health outcomes. Indicators of mental health were suicide rates, alcohol consumption and tobacco use. Indicators of physical health included life expectancy, infant mortality rates, and prevalence of HIV. Using pathway analysis on international data from a selected sample of European, North American, South American and South Caucasus countries, similar models for mental health and physical health were developed. In the first model, the positive effects of socioeconomic status and social capital on physical health were completely mediated via rights and freedoms. In the second model, the positive effect of socioeconomic status on mental health was completely mediated, while the impact of social capital was partially mediated through rights and freedoms. We named the models, the “rights and freedoms gradient of health” in recognition of this latter construct’s crucial role in determining both physical and mental health.